BILANGAN DOMINASI DAN BILANGAN KEBEBASAN GRAF BIPARTIT KUBIK - Santoso, Budi; Djuwandi, Djuwandi; S.U, Robertus Heri (MATEMATIKA, 2012)
Let a graph , is a pair of sets V vertices and set E edges. Let  be a subset of . If each vertex of  is adjacent to atleast one vertex of , then  is called a dominating set in . The domination number of a graph  denoted as  is the minimum cardinality of a dominating set in . A set of vertices in a graph is said to be an independent set if no two vertices in the set are adjacent. the number of vertices in the largest independent set of a graph  is called the independence number and denoted by . In this final project, we consider the relation between independent set and dominating set of finite simple graphs. In particular, discuss them for some cubic bipartite graphs and find that the domination number is less than  of the number of vertices and independence number  is half of the number of vertices.